Optimal Design of Photoelectric Rotating-speed Sensor at Axle End of Locomotive - WU Cheng-shu; MI Zhi-nan; YE Ming-sheng; ZHANG Yan-liang; GONG Yun-sheng (机车电传动)
According to the fault of photoelectric rotating-speed sensor based on TB/T 2760-1999 after locomotive speedup, new technology and material utility of high-speed encoder was adopted for product integral optimized design. Collective structure and main technical specification of the optimized sensor was introduced. Experiment and batch on-board examination proved that the new product had good performance and satisfied the design requirement of every index.